Synthesis and Structural Studies of Some Inorganic Polymers of Succinoyl Carboxymethyl Cellulose - H. D. Juneja; Manisha Joshi; N. T. KhatiI (E-Journal of Chemistry)
The inorganic polymers containing transition metals such as Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) were synthesized by using succinoyl carboxymethyl cellulose (SCMC) in aqueous media. The newly synthesized polymers were characterized by elemental analysis, IR spectroscopy, TG analysis, UV reflectance spectra and magnetic moment. On the basis of these studies, the composition of the polymeric unit was found to be [M(II)L]n, [Mʼ(II)L.2H2 O]n, {[Mˮ(II)L.2H2O]n H2O}, where M= Zn(II), Mʼ = Mn(II), Ni(II) and Cu(II) and Mˮ = Co(II), L = SCMC ligand. On the basis of instrumental techniques, it has been found that the [Zn(II)(SCMC)]n inorganic polymer has tetrahedral geometry, whereas {[Cu(II)(SCMC)].2H2O}n has square planar geometry and [Mn(II)(SCMC).2H2O]n, {[Co(II)(SCMC).2H2O)].H2O}n and [Ni(II) (SCMC).2H2O]n have octahedral geometry. The decomposition temperatures of the inorganic polymers have been determined by TGA. The TGA reveal that the Mn(II) polymer of SCMC is highly thermally stable than rest of the polymers and these polymers can be used as thermal resisting materials.